Correspondence: the importance of supplication for parents in the Neonatal Intensive Care Unit - Hüseyin Çaksen (Journal of Pediatric and Neonatal Individualized Medicine, 2021)
The Neonatal Intensive Care Unit (NICU) often causes stress, anxiety and fear for parents during hospitalization of their infant. Religion and spirituality are important for many parents and to make the infant healthier and normal they pray God. Supplication is the spirit of worship and results from sincere belief.